Cardiac Effusion after Repair of Morgagni and Hiato´s Hernia by Laparoscopy (European Journal of Health Research, 2021)
Morgagni's hernia is a malformation that occurs in 3-5% of diaphragmatic hernias, most of which are asymptomatic. Laparoscopic repair has several advantages over traditional treatment. The complication rate is below 5%. Cardiac tamponade is a rare complication after laparoscopic surgery.We present a case of a woman who, after undergoing laparocopy for a Morgagni hernia, suffered cardiac tamponade. An emergency approach was performed, using a sternotomy, and the Tacker device that caused the effusion by laceration of the right ventricle through the diaphragm was removed.
Keywords: hernia; tracker; Cardiac Effusion; Morgagni hernia; heart